2014
DOI: 10.1055/s-0034-1372599
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Gene Expression in Peripheral Blood Mononuclear Cells from Children with Type 1 Diabetes in 3 Periods

Abstract: To explore the expression changes of potential key genes and relevant biological processes in peripheral blood mononuclear cells of children with newly diagnosis of type 1 diabetes (T1D).Microarray data GSE9006 were downloaded from Gene Expression Omnibus (GEO) database, including peripheral blood mononuclear cells samples from 43 children with newly diagnosed T1D (NEW), 19 one-month (1-MO) follow-up samples, 19 4-month (4-MO) follow-up samples and 24 healthy controls. The differentially expressed genes (DEGs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…26 Previous microarray studies showed that KLRF1 and KLRD1, expressed by natural killer (NK) cells, were dysregulated in PBMCs of T1D subjects. 27,28 The high correlation between HLA-DRB4 and T1D has been widely accepted, with HLA-DRB4 essential in self-versus non-self-immune recognition. [29][30][31] Of note, ZBTB16 was identified as a significant hub protein in the key T1D gene network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Previous microarray studies showed that KLRF1 and KLRD1, expressed by natural killer (NK) cells, were dysregulated in PBMCs of T1D subjects. 27,28 The high correlation between HLA-DRB4 and T1D has been widely accepted, with HLA-DRB4 essential in self-versus non-self-immune recognition. [29][30][31] Of note, ZBTB16 was identified as a significant hub protein in the key T1D gene network.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MAFB is implicated in enterovirus infections through regulation of transcription of type I interferon, predisposing human islet cells to coxsackievirus infection or persistence, thus increasing susceptibility to T1D . Previous microarray studies showed that KLRF1 and KLRD1 , expressed by natural killer (NK) cells, were dysregulated in PBMCs of T1D subjects . The high correlation between HLA‐DRB4 and T1D has been widely accepted, with HLA‐DRB4 essential in self‐ versus non‐self‐immune recognition …”
Section: Discussionmentioning
confidence: 99%
“…Type 1 diabetes mellitus (T1DM) is an important health problem with an increasing incidence worldwide [1,2]. The insulin-producing pancreatic beta cells are destroyed in individuals with T1DM resulting in lifetime dependence of exogenous insulin [2,3]. Type 1 diabetes, as a serious and lifelong disorder leads to a lot of systemic complications [4,5].…”
Section: Introduction ▼mentioning
confidence: 99%
“…Nonetheless, our study gives a unique insight into in vivo gene expression. Based on the data by Liu et al, 44 we can estimate which cell type is responsible for the observed changes in gene expression. Similarly, there are tools for a post hoc extrapolation of mixed -cell population lines in epigenetic studies.…”
Section: Results Of Gene Expression According To Fat Valuementioning
confidence: 99%